China's growing engagement with the UNDS as an emerging nation: Changing rationales, funding preferences and future trends - Ruipeng Mao (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
As China deepens its engagement in global governance and development, its strategic motivation and rising influence within the UN and on international rules and norms are attracting the world's attention. This paper focuses on China's engagement with the UNDS, specifically Chinese funding and allocation decisions. China's UNDS funding has risen rapidly since 2008 and even accelerated in 2013. Between 2013 and 2017, Chinese funding (excluding local resources) grew at an annual average rate of 33.8 per cent. In 2017, its total contribution reached USD 325.869 million. China's shares of core funding and assessed contribution in its total UNDS funding are much higher than traditional donor countries. However, the share of non-core funding has also jumped. While China tends to mostly provide funds for UNDS development projects, in recent years it has also been hiking funding for humanitarian assistance. This paper also examines three cases of China's earmarked funding - to the UNDP and the WFP, which receive the largest share of its UNDS funds, as well as for UNPDF operations, which count as a voluntary contribution. There are several reasons for China's growing engagement with the UNDS, from evolving perception of foreign aid and appreciating the UN's multilateral assets to fostering the reputation of "responsible great nation" and pushing forward the Belt and Road Initiative (BRI) through cooperation with the UNDS. In general, China continues to integrate into the global development system, and can be expected to maintain its support for the UN and continue to contribute to the UNDS.
Keywords: 330